If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27.24 = 5g + 3.84 Reorder the terms: 27.24 = 3.84 + 5g Solving 27.24 = 3.84 + 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. 27.24 + -5g = 3.84 + 5g + -5g Combine like terms: 5g + -5g = 0 27.24 + -5g = 3.84 + 0 27.24 + -5g = 3.84 Add '-27.24' to each side of the equation. 27.24 + -27.24 + -5g = 3.84 + -27.24 Combine like terms: 27.24 + -27.24 = 0.00 0.00 + -5g = 3.84 + -27.24 -5g = 3.84 + -27.24 Combine like terms: 3.84 + -27.24 = -23.4 -5g = -23.4 Divide each side by '-5'. g = 4.68 Simplifying g = 4.68
| 82=5y+17 | | 142=(3x)+(2x+10)+x | | 2(x+5)(x-4)=0 | | -7x+6=-9x | | 4r^2+6x-8=0 | | 0=7x^2+27x-4 | | -12x+13+21x+2=180 | | 4w-14=18 | | 6x+x^2-7=-16 | | 7p+9q=6r | | k+6=31 | | 54=10u-u | | -3x+31=-7x-9 | | 48p=-8 | | 1.4y-3.7=0.6y+2.54 | | -n-2=-15 | | p-6u+3-4u+9p+14= | | -0.15x^2+150x=11000 | | -2=3+5x | | -0.15x^2+150x= | | x(x+4)=-20 | | 10(-0.2)+4=2(2) | | 3u+2u=25 | | 2(42x+2y)x(52x+3y)-(33x+6y)= | | 10(-0.4)+4=2(2) | | 21+7g=98 | | 15n^2+3n=0 | | -3(k-12)=48 | | 5x+12+6x-10=120 | | 10(-2.5)+4=2(2) | | 7x+3+72=180 | | 3+5+x-3=6+8-3+1 |